2016
DOI: 10.1111/1471-0528.14213
|View full text |Cite
|
Sign up to set email alerts
|

Maternal tobacco use and extremely premature birth – a population‐based cohort study

Abstract: Tobacco use increases risk of extremely preterm birth. Cessation is preventive. Avoid nicotine in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 44 publications
(100 reference statements)
2
56
1
2
Order By: Relevance
“…Previous studies on maternal snuff use are based on early pregnancy data on snuff use in the MBR . However, cotinine levels in maternal urine in week 32 reflect tobacco exposure in the last trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on maternal snuff use are based on early pregnancy data on snuff use in the MBR . However, cotinine levels in maternal urine in week 32 reflect tobacco exposure in the last trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the MBR of self‐reported snuff use have been associated with increased risks of adverse fetal and neonatal outcomes, including stillbirth, preterm birth, neonatal apnea, and oral cleft malformations . The perceived social stigma of tobacco use in pregnancy may increase the risk of underreporting, so leading to bias .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the use of snus in pregnancy reported in the three countries with available data was <1% in the USA, 1.1% in Sweden and 3.4% in Norway .…”
Section: Resultsmentioning
confidence: 89%
“…The three studies reporting the prevalence of snus use in or after pregnancy included one population‐based cohort from Sweden, one from the USA and one register study from Norway (Table ). Data were obtained from national birth register , a survey and electronic birth records based on self‐reports by the study subjects. The number of respondents ranged from 388 to 1 371 274.…”
Section: Resultsmentioning
confidence: 99%
“…Women who continue to smoke through pregnancy are at increased risk of placental abruption [7,12], an infant with low birth weight and preterm birth before 37 weeks gestation [7,13]. Australian evidence suggests the pregnant women least likely to cease smoking are the young, socioeconomically disadvantaged and Aboriginal and Torres Strait Islanders [14].…”
Section: Introductionmentioning
confidence: 99%